Proton detection of carbon-carbon couplings in symmetrical molecules: Analytical explanation, SYMONA pulse sequence - Blechta, Vratislav; Sýkora, Jan (Journal of magnetic resonance (San Diego, Calif., 2019)
The approach to the measurement of one-bond indirect spin-spin coupling constants between equivalent nuclei was revisited. The analytical formulas for development of the density matrix of strongly coupled symmetrical HC-C'H' spin systems were derived and the optimal duration of polarization delay in the original 2QHMBC pulse sequence is discussed. Based on the analytical formulas a new version of a robust indirect detection experiment, called SYMONA (SYmmetrical MOlecules Natural Abundance double-quantum experiment), was proposed for carbon-carbon coupling constants detection in symmetrical molecules. Additionally, application of the SYMONA experiment to more complicated spin systems than isolated HC-C'H' is discussed.
Keywords: NMR; 2QHMBC; SYMONA; Proton detection; Strong coupling; Equivalent carbons; Carbon-carbon coupling